Recent advances in construction of small molecule-based fluorophore-drug conjugates - Wenjie Lang; Chaonan Yuan; Liquan Zhu; Shubo Du; Linghui Qian; Jingyan Ge; Shao Q. Yao (Elsevier, 2020)
As a powerful tool to advance drug discovery, molecular imaging may provide new insights into the process of drug effect and therapy at cellular and molecular levels. When compared with other detection methods, fluorescence-based strategies are highly attractive and can be used to illuminate pathways of drugs' transport, with multi-color capacity, high specificity and good sensitivity. The conjugates of fluorescent molecules and therapeutic agents create exciting avenues for real-time monitoring of drug delivery and distribution, both in vitro and in vivo. In this short review, we discuss recent developments of small molecule-based fluorophore-drug conjugates, including non-cleavable and cleavable ones, that are capable of visualizing drug delivery.